Snow Leopard habitat vulnerability assessment under climate change and connectivity corridor in Xinjiang Uygur autonomous region, China - Wei Cong; Jia Li; Yi Zhang; Taifu Huang; Shuaishuai Gao; Jianhua Yu; Yuguang Zhang; Diqiang Li (Scientific Reports)
Abstract Climate change is recognized as one of the greatest challenges to global biodiversity. The endangered snow leopard (Panthera uncia), an apex predator in high-altitude mountain ecosystems, serves as an important indicator of ecological health. Understanding the impacts of climate change on snow leopard distribution patterns is essential for developing effective conservation strategies. Based on the BIOMOD2 model, this study assesses the current distribution of suitable habitats and project future changes under various climate scenarios, as well as evaluates the protection gap and corridor construction in Xinjiang Uygur Autonomous Region, China. The results indicated the total area of suitable habitat for snow leopard in Xinjiang is approximately 686,200 km2 under the current climate conditions. The area of suitable habitat remains relatively stable or slightly increases under low emissions scenarios, while predictions show a gradual decline under moderate and high emissions scenarios. Currently, suitable habitats are fragmented, with low connectivity among patches, posing threats to the snow leopard population. Vulnerable habitats are primarily located in the Altai, northwestern Junggar Basin, and the central Tianshan Mountains. Potential future suitable areas are projected emerge in the Kunlun Mountains. It is suggested that greater focus be placed on unprotected climate refugia, enhancing the connectivity of habitat corridors, fostering cross-border cooperation, and implementing long-term monitoring efforts. This study provides valuable insights for conservation strategies aimed at mitigating the impacts of climate change on snow leopard populations in Xinjiang, China.